2018
DOI: 10.1039/c7ta09798k
|View full text |Cite
|
Sign up to set email alerts
|

Electric field effect on the microstructure and properties of Ba0.9Ca0.1Ti0.9Zr0.1O3 (BCTZ) lead-free ceramics

Abstract: Systematic evaluation of the effect that electric field application has on the structure, microstructure and piezo-ferroelectric properties of barium titanate-based lead-free piezoelectric ceramics reveals a field-induced phase transition underlying its high sensibility.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 26 publications
(7 citation statements)
references
References 46 publications
2
5
0
Order By: Relevance
“…The slightly smaller values of k t and d 33 in Table compared with the current literature may be due to the chemical inhomogeneity in triple grain junctions of the ceramics in this study, which was revealed by exhaustive EDS analysis (Figure S1). However, the overall performance is similar to that reported for BCTZ ×10 ceramic with similar grain size obtained by the Pechini method . These results show that the electromechanical activity of BCTZ strongly depends, in addition to the specific composition, on its crystal and ceramic microstructure.…”
Section: Resultssupporting
confidence: 86%
See 1 more Smart Citation
“…The slightly smaller values of k t and d 33 in Table compared with the current literature may be due to the chemical inhomogeneity in triple grain junctions of the ceramics in this study, which was revealed by exhaustive EDS analysis (Figure S1). However, the overall performance is similar to that reported for BCTZ ×10 ceramic with similar grain size obtained by the Pechini method . These results show that the electromechanical activity of BCTZ strongly depends, in addition to the specific composition, on its crystal and ceramic microstructure.…”
Section: Resultssupporting
confidence: 86%
“…The domains are identified as a lamellar typelike shape with a domain width ( d ) value average of ∼1 μm, Figure d. High-resolution (HR) images display a lamellar typelike domain structure (Figure e), already reported for BaTiO 3 single crystals , or other BCTZ compositions . Considering a classical approach for ceramic samples, it is well-known that the domain width, d , is related to the grain size, G , as d ∼ .…”
Section: Resultsmentioning
confidence: 67%
“…final draft post-refereeing) of the publication. The final publication is available at Elsevier via http://dx.doi.org/10.1016/j.jallcom.2018.10.060 7 temperature, which is similar to that in previous works [11,27]. The inset of Fig.…”
Section: Introductionsupporting
confidence: 84%
“…Materials possessing an MPB composition can have a comparatively high piezoelectric coefficient due to the rotational and contractional transitions of domains. , To further investigate the phases of the BCTZ NPs, their Raman spectrum was characterized, as shown in Figure d. The sharp peaks of the E, B 1 (TO+LO) modes at 300 cm –1 ; E, A 1 (TO) modes at 520 cm –1 ; and E, A 1 (LO) modes at 720 cm –1 indicate the existence of a tetragonal phase in the BCTZ NPs. Note that the discrepancy between the XRD result and the Raman spectrum is caused from the coexistence of multiple phases due to the MPB composition of the BCTZ NPs …”
Section: Resultsmentioning
confidence: 99%